2018
DOI: 10.17323/2411-7390-2018-4-2-48-58
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Mobile Assisted Language Learning on Learner Autonomy in EFL Reading Context

Abstract: Traditional classrooms confine English as a Foreign Language (EFL) reading to the textbook and the classroom setting, something that demotivates active reading. With the advent of mobile technology, however, such boundaries can be broken to include external reading materials where students could read and share anytime and anywhere. This paper investigates the role of mobile technology in enhancing Learner Autonomy (LA) in the EFL reading context among students in the Preparatory Year (PY) of Najran University … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
37
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 23 publications
7
37
0
1
Order By: Relevance
“…This is a chief advantage of MALL that it provides independence to the learners and Pakistani students also are of the view that MALL provided them independence and freedom to learn according to their own pace and willingness related to context and ambiance. This argument of Pakistani students is also similar to the study conducted by Hazaea and Alzubi (2018), who found out that the feeling of autonomy was increased amongst learners during their learning process.…”
Section: Discussionsupporting
confidence: 85%
“…This is a chief advantage of MALL that it provides independence to the learners and Pakistani students also are of the view that MALL provided them independence and freedom to learn according to their own pace and willingness related to context and ambiance. This argument of Pakistani students is also similar to the study conducted by Hazaea and Alzubi (2018), who found out that the feeling of autonomy was increased amongst learners during their learning process.…”
Section: Discussionsupporting
confidence: 85%
“…23 Han & Keskin (2016) Conducting tasks in EFL speaking courses for four weeks. 24 Hazaea & Alzubi (2016) Leaners were kept in contact with each other with regard to our reading class 25 Hazaea & Alzubi (2018) Tasks and assignments were conducted by learners outside the classroom. The learners searched the internet about topics of their choice and share them for interaction with peers and teachers" feedback.…”
Section: Results Concerning the Utilisation Of Whatsapp For Language mentioning
confidence: 99%
“…Some of the studies (e.g. Awada, 2016;Hazaea & Alzubi, 2018) utilized more than one data collection tool. Some studies (e.g., Ahmed, 2019;Allagui, 2014) utilized surveys and questionnaires to support the empirical data.…”
Section: Data Setsmentioning
confidence: 99%
“…Past research demonstrates that MALL influences vocabulary learning systems, self-governance, and reading comprehension [26]. Similarly, to access new content-ondemand there is a need for Internet access that allows the user to do so whereas it requires the capability for doing such is pointed by [43].…”
Section: F Mobile-assisted Language Learning (Mall)mentioning
confidence: 99%